Highly stable and blue-emitting copper nanocluster dispersion prepared by magnetron sputtering over liquid polymer matrix. Issue 107 (3rd November 2016) - Porta, Matteo; Nguyen, Mai Thanh; Ishida, Yohei; Yonezawa, Tetsu
Abstract : For the first time, magnetron sputtering of copper onto liquid was investigated for the preparation of stable blue-fluorescent copper nanoclusters. Abstract : For the first time, magnetron sputtering of copper onto liquid was investigated for the preparation of stable blue-fluorescent copper nanoclusters. The fluorescent intensity increased linearly with an increase of mercaptan. Our finding casts light on the formation mechanism of metal photoluminescent nanoclusters via sputtering onto liquid.